Viral Load Pattern and Virological Suppression Rate of a Cohort of Hiv-1 Patients in a Rural Community in Nigeria - Babatope, I. O.; Esumeh, F. I.; Orhue, P. I.; IYEVHOBU, KENNETH (European Journal of Applied Sciences, 2022)
HIV is a pandemic infection and remains a public health concern for many decades. This infection is associated with life threatening depletion of immune response, opportunistic infections and malignancies. The aim of this study is to determine the viral load pattern and virological suppression rate of HIV-1 subjects in Irrua, Edo Central Senatorial District of Edo state, Nigeria. A total of three hundred and forty four (344) HIV-1 subjects aged between 17-60 years and of both sexes were recruited into the study. The HIV-1 subjects were divided into asymptomatic and symptomatic subjects. One hundred and fifty (150) apparently healthy HIV-1 negative subjects served as control. The viral load titre was determined using the COBAS Ampliprep/COBAS “Taqman” HIV-RNA test (PCR technology). Results obtained revealed that the mean viral loads of the asymptomatic and symptomatic HIV-1 subjects were 20,333.00±13,474.65 and 535,000.02±485,423.40 against control (20.00±0.00). Both asymptomatic and symptomatic groups revealed a statistical significant difference (P<0.05). Furthermore, there was no significant difference according to gender while comparison between viral load and age showed a statistically significant difference (P<0.05).The overall virological suppression rate of HIV-1 subjects on-ART was 81.6%. Sex-wise distribution revealed that more females (48.87%) were virally suppressed compared to their male counterparts (32.73%). According to age distribution, subjects belonging to the age bracket of 37-46 years recorded the highest frequency distribution of 37.96% while the least (5.70%) belonged to the age group of 17-26 years. In summary, there was a significant and progressive increase in the viral load titre of asymptomatic and symptomatic HIV-1subjects in relation to control. Also, the proportion of HIV-1 subjects who had viral load <1,000 RNA copies/ml was relatively high at 81.6% but falls short of UNAIDS’ 90% target for on-treatment viral suppression. It re-emphasizes the need to test subjects and start treatment with antiretroviral drugs early.